Self-Presentation as the Modus Vivendi of a Magnanimous Man - Drabarek, Anna (Eidos. A Journal for Philosophy of Culture, 2025)
The article discusses satisfaction with self-presentation as the way of functioning (modus vivendi) of a magnanimous man in relation to Aristotelian ethics. Even though self-presentation is usually considered as a kind of biologically determined instinct, it may be argued that self-presentation is also an aspect of the actions of a magnanimous man. Naturalist social theories concerning moral norms are rooted in nineteenth and twentieth century psychologism, which claims that the starting point for reflection on the nature of social morality are the psychical characteristics of individuals. One example of psychologism is the concept of Sorokin who compares two basic mentalities determining culture: sensate and ideational. On the other hand, there are theories in the current of normative naturalism which postulate a reduction of ethical values to certain biological – mostly psychological – properties or states. This current includes Portmann’s theory referring to the instinct of self-presentation discussed in this article. Portman’s reflections are confirmed by the cultural concept of homo ludens proposed by Huizinga. Self-presentation may be considered not only as a biologically determined instinct on the grounds of normative naturalism, but also on the grounds of realist ethics as a value in itself, non-reducible to any particular biological facts. It is in the perspective of Aristotle’s ethics of virtue that self-presentation becomes an expression of the actions of a magnanimous man correlated with ethical value, as it recognizes satisfaction with self-presentation as a state that depends on the success of human activity. This explains why it is satisfaction, or pleasure, or happiness that can be reasonably regarded as the goal of human life. Satisfaction is an emotion that accompanies the achievement of perfection in various forms of human activity. However, satisfaction, pleasure, or happiness are not, in this context, a criterion that determines our behavior, for satisfaction alone is not a reason to perform a particular type of activity. What one finds satisfaction in depends primarily on the virtues one possesses. This is why self-presentation becomes an ethical value only in the case of a magnanimous man, one of an ideational mentality; in the case of a proud man, one of a sensate mentality, self-presentation proves to be an anti-value. An embodiment of this latter attitude in modern liberal democracy is Ortega y Gasset’s arrogant mass-man, as well as the mass-man engulfed in apathy described by Sloterdijk.